The INFLUENCE of GLOBALISATION to LOCAL CULTURE - Ahmad Muthalib (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Globalization is a phenomenon which happens in modern society. It spreads around the world in line with the progress of the society since it moves through many media such as television, internet, hand phone, newspaper, transportation, and others. Since the existence of globalization could not be stopped, then a solution to keep local culture is every people should keep his faith to God. Furthermore, the government and all social elements have to play an active role to watch the globalization process. However, it depends on every people in the society.